Kairos, Crisis, and Global Apartheid - Boesak, Allan Aubrey. author. aut Link
IX, 272 p.
Keywords: In 1985, the Kairos Document emerged out of the anti-apartheid struggle as a devastating critique of apartheid and a challenge to the church in that society. This book is a call to discern new moments of crisis, discernment and kairos, and respond with prophetic resistance to global injustice.